THE USE OF INSTAGRAM SOCIAL MEDIA IN REGIONAL TOURISM BRANDING: A STUDY OF THE @visit.langkat ACCOUNT - Stevani Stevani; Lies Utami Efni Safitri (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze the use of Instagram as a tool for regional tourism branding through the @visit.langkat account using the Stimulus-Organism-Response (SOR) theory approach. The research employs a descriptive qualitative method with data collection techniques including observation, in-depth interviews, and documentation. The results show that visual content such as photos and videos of natural attractions, adventure activities, and tourist experiences serve as effective stimuli in attracting audience attention. These stimuli are processed by the audience, leading to the formation of positive perceptions of Langkat Regency tourism, such as being natural, attractive, and diverse. The responses generated include increased interest in visiting, curiosity, and actions to seek further information about the destinations. However, the study also finds limitations in the lack of detailed information regarding access, ticket prices, and facilities. Overall, Instagram is proven to be an effective medium for tourism branding, but it needs to be supported by more complete and consistent information delivery.